THE IMPLEMENTATION OF MARKETING COMMUNICATION IN ATTRACTING PROSPECTIVE STUDENTS INTEREST TO STUDY AT VOCATIONAL HIGH SCHOOL - Daradjat, dkk, Ridwan Setiawan; Hafiar, Hanny (EDUTECH, 2015)
Abstract, Research is entitled "Implementation of Marketing Communications In Attracting Prospective Students Attended School in SMK". Focus of this research is how the implemementation of marketing communications The focus of this research is how the implementation of marketing communications activities undertaken by Wakasek Ur. Hubinmas in attracting prospective students to attend school in SMKN 2 Garut. This research explains the framework of Wakasek Ur. Hubinmas SMKN 2 Garut efforts implementing marketing communication school to attract the interest of prospective students to attend school in SMKN 2 Garut. Research questions are : (1) How Intepretation of interviewees regarding education in SMKN 2 Garut. (2) What communications channels are used to attract the interest of prospective students to attend school in SMKN 2 Garut. (3) How the communications pattern is done in net interest prospective students to attend school in SMKN 2 Garut. The conceptual framework in this study are: marketing communications, Industry Relations and society (Hubinmas), Student Interest in SMK. The research method used is descriptive qualitative method by using a case study approach, with research method there using is descriptive qualitative with case study.The result of research and the exposure in the form of : (1) Knowing the intepretation informan abaout education in SMKN 2 Garut. (2) Knowing the communications channel will using to attract prospective students to study in SMKN 2 Garut  (3) Knowing the communications pattern doing to attract prospective students to study in SMKN 2 Garut.Conclusion of this research is intepretation the interviewees regarding education in SMK including the performance of teachers and teachers quality improvement, developing talents and skills provision face competition, institutions of formal education, in addition according to the wishes and the capabilities of prospective students, have many advantages ready to work. Communication channels used in the form of Garut's radio and local newspaper, social media, socialization to junior high school and MTs, Job Matching, training teachers in the form of Educational activities of the teaching profession, Teacher education and Professional Training, socialization/training quality teachers with In House Training, brochures, banners, Website. Communication pattern of In House Training for teachers, Ujikom and Prakerin for students, and job fair specially alumni, socialization PPDB to junior and MTs, brochures, banners, social media, and websites, in collaboration with the LSP establishment BNSP ujikom testers, requests, and the flagship program. Key Words : Implementation, Communication, Understanding, Channel, Pattern.  Abstrak, Penelitian ini berjudul Implementasi Komunikasi Pemasaran Dalam Menarik Minat Calon Siswa Bersekolah di SMK. Fokus penelitian ini ialah bagaimana implementasi kegiatan komunikasi pemasaran yang dilakukan oleh Wakasek Ur. Hubinmas (dianggap mewakili sekolah,jd tdk perlu dicantumkan) dalam menarik minat calon siswa untuk bersekolah di SMKN 2 Garut. Kerangka penelitian ini menjelaskan upaya Wakasek Ur. Hubinmas SMKN 2 Garut mengimplementasikan komunikasi pemasaran sekolah untuk menjaring minat calon siswa untuk bersekolah di SMK Negeri 2 Garut(dihilangkan sj langsung ke pertanyaan penelitian), Adapun pertanyaan penelitian diantaranya : (1) Bagaimana pemahaman  nara sumber mengenai pendidikan di SMKN 2 Garut. (2) Bagaimana saluran komunikasi yang digunakan untuk menjaring minat calon siswa untuk bersekolah di SMKN 2 Garut. (3) Bagaimana pola komunikasi yang dilakukan  dalam  menjaring minat calon siswa untuk bersekolah di SMK Negeri 2 Garut. Kerangka Konseptual dalam penelitian ini adalah : Komunikasi Pemasaran, Hubungan Industri dan Masyarakat (Hubinmas), Minat Siswa Bersekolah di SMK.(dihilangkan saja) Metode penelitian yang digunakan ialah metode kualitatif deskriptif dengan menggunakan pendekatan studi kasus. Hasil penelitian dan pembahasan berupa (1) Mengetahui Pemahaman  narasumber mengenai pendidikan di SMKN 2 Garut. (2) Mengetahui saluran komunikasi apa saja yang digunakan untuk menjaring minat calon siswa untuk bersekolah di SMKN 2 Garut. (3) Pola komunikasi yang dilakukan  dalam  menjaring minat calon siswa untuk bersekolah di SMKN 2 Garut.(dihilangkan saja)Kesimpulan penelitian ini ialah(dihilangkan saja) Hasil penelitian ini diperoleh pemahaman nara sumber mengenai pendidikan di SMK yaitu kinerja guru dan peningkatan mutu guru, mengembangkan bakat dan keahlian bekal menghadapi persaingan, lembaga pendidikan formal, penjurusan sesuai keinginan dan kemampuan calon siswa, memiliki banyak keunggulan, siap untuk bekerja. Saluran komunikasi yang digunakan berupa radio, koran lokal Garut, sosial media, sosialisasi ke SMP dan MTs, Job Matching, Kegiatan pembinaan guru berupa Pendidikan Keprofesian Guru, Pendidikan dan Latihan Profesi Guru, sosialisasi/pembinaan mutu guru, dan In House Training, brosur, spanduk, Website. Pola komunikasinya berupa In House Training guru, Prakerin dan Ujikom siswa, Bursa Kerja Khusus alumni, sosialisasi PPDB ke SMP dan MTs, brosur, spanduk, sosial media, dan website, kerjasama pendirian LSP dengan BNSP, permohonan penguji ujikom, dan program unggulan.Kata-kata kunci : Implementasi, Komunikasi, Pemasaran, Minat, Bersekolah.